Efek Kepemimpinan Spiritual Terhadap Kinerja Dimediasi Oleh Etos Kerja Pegawai - Korip, Fatkul; Adriani, Zulfina; Khalik, Idham (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the effect of spiritual leadership on employee performance with work ethic as a mediating variable at the Bram Itam Sub-district Office, Tanjung Jabung Barat Regency. The research method used is quantitative with a saturated sampling technique involving 37 respondents. Data was collected through questionnaires and analyzed using descriptive methods and Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the study indicate that spiritual leadership does not have a direct significant effect on employee performance but has a positive and significant effect on work ethic. Furthermore, work ethic has a positive and significant effect on employee performance and significantly mediates the relationship between spiritual leadership and employee performance.